2015
DOI: 10.4028/www.scientific.net/amm.773-774.734
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Gadolinium Doped Zinc Oxide Nanorods Thin Films

Abstract: Abstract.ZnO nanorods (NRs) arrays were synthesized by chemical solution deposition (CSD) method on commercial glass substrate with ZnO thin film act as seed layer prepared by sol-gel spin coating. The effect of annealing temperature of 150°C, 250°C and 500°C, respectively, on the structural growth was investigated. The observation reveals the structural improvement as the annealing temperature increased. The influence of gadolinium doping to ZnO NRs arrays wasexplored upon the structural and optical features.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Our study reports facile synthesis route of Gd 3+ doped ZnO-NRs and the study of its essential properties. To the knowledge of the authors, only a few scholars [27][28][29] have reported the preparation of rod-like shape Zn 1Àx Gd x O (x ¼ 0.03 and 0.06).…”
Section: Introductionmentioning
confidence: 99%
“…Our study reports facile synthesis route of Gd 3+ doped ZnO-NRs and the study of its essential properties. To the knowledge of the authors, only a few scholars [27][28][29] have reported the preparation of rod-like shape Zn 1Àx Gd x O (x ¼ 0.03 and 0.06).…”
Section: Introductionmentioning
confidence: 99%
“…Group III elements, including as Ga, Al, and In, which can be utilised as n-type dopants in ZnO, have long been known to affect the material's optical and electrical properties [13]. Rare earth elements, such as Ce, Er, Eu, La, Tb, Tm, Yb, and Dy as p-type dopants in ZnO, have also piqued interest due to their distinctive optical properties, which result in high emission peaks in the visible and near infrared range [14]. As a result, doping can be used to change the electrical conductivity, type of conduction and band gap range of the nanomaterial, as well as its magnetic properties.…”
Section: Introductionmentioning
confidence: 99%